1985
DOI: 10.1002/ajpa.1330660304
|View full text |Cite
|
Sign up to set email alerts
|

Cortical bone maintenance and geometry of the tibia in prehistoric children from Nubia's Batn el Hajar

Abstract: The relationship between advancing age in adults and patterns of cortical bone maintenance has been extensively documented for archaeological populations (Dewey, et al., 1969; Van Gerven et al., 1969; Perzigian, 1973). Most recently, this research has been expanded to include a more thorough consideration of the geometric properties of bone in relationship to adult age changes (Martin and Atkinsin, 1977; Ruff and Hayes, 1983). To date, however, few studies have documented subadult patterns of cortical bone mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 17 publications
4
38
0
Order By: Relevance
“…There is some evidence from the archaeological Nubian material that suggests that some type of compensatory mechanism was occurring with the reduction in bone mass to prevent a compromise in bone quality. For example, investigation of cortical maintenance in prehistoric Nubian children found that growth mechanisms were able to compensate for observed nutrition-related and modeling bone loss to maintain bone quality (Van Gerven et al, 1985).…”
Section: Archaeological Populationsmentioning
confidence: 99%
“…There is some evidence from the archaeological Nubian material that suggests that some type of compensatory mechanism was occurring with the reduction in bone mass to prevent a compromise in bone quality. For example, investigation of cortical maintenance in prehistoric Nubian children found that growth mechanisms were able to compensate for observed nutrition-related and modeling bone loss to maintain bone quality (Van Gerven et al, 1985).…”
Section: Archaeological Populationsmentioning
confidence: 99%
“…It was then that large-scale studies on the nature and rate of bone loss in North African prehistoric and historical human groups from Sudanese Nubia were planned. The studies resulted in numerous detailed and exhaustive works (Dewey et al, 1969a,b;Armelagos et al, 1972Armelagos et al, , 1982Mielke et al, 1972;Martin & Armelagos, 1979;van Gerven et al, 1985). Parallel to the above mentioned studies, research on human bone remains from the North American continent was initiated.…”
Section: Bone Tissue Involution In Skeletal Populationsmentioning
confidence: 99%
“…Cortical thickness has been used as an osteological indicator of stress (Cox et al, 1983), particularly nutritional stress, albeit to a much lesser extent than other markers such as stature or dental enamel hypoplasias. Most workers studying cortical bone as a stress indicator have focused on patterns of growth in cortical thickness, using juvenile skeletons (Cook, 1979;Huss-Ashmore et al, 1982;Hummert, 1983;van Gerven et al, 1985;Mays, 1985Mays, , 1995Mays, , 1999a. Some studies of adult remains have also taken this perspective (Hatch et al, 1983;Pfeiffer and King, 1983;Owsley, 1991), deficiencies of peak cortical bone in adulthood being taken as indicators of unfavorable conditions during the growth period.…”
mentioning
confidence: 99%